2020
DOI: 10.16993/sjdr.648
|View full text |Cite
|
Sign up to set email alerts
|

Supported Education in a Swedish Context – Opportunities and Challenges for Developing Career-Oriented Support for Young Adults with Mental Health Problems

Abstract: Young adults experiencing mental health problems often need both individual support and educational accommodations to successfully complete their studies. Recent research also points to the need for careerrelated, educational services in a labor market that increasingly demands formal education or training.The aim of this study was to investigate the development of supported education services in Sweden, in relation to pursuing educational and vocational goals. Interviews were conducted with a broad sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Several of the studies suggested a need to work with attitudes regarding mental health challenges for students, since among educational actors, there is an impression that higher education may not be an achievable goal for some of these individuals (e.g. [5,36,39]). Students described a variety of challenges and needs, such as a lack of knowledge about the services available at universities [13], or that they felt insecure in discussing their mental health challenges and seeking available supports (e.g.…”
Section: Needs and Challenges In An Educational Contextmentioning
confidence: 99%
See 4 more Smart Citations
“…Several of the studies suggested a need to work with attitudes regarding mental health challenges for students, since among educational actors, there is an impression that higher education may not be an achievable goal for some of these individuals (e.g. [5,36,39]). Students described a variety of challenges and needs, such as a lack of knowledge about the services available at universities [13], or that they felt insecure in discussing their mental health challenges and seeking available supports (e.g.…”
Section: Needs and Challenges In An Educational Contextmentioning
confidence: 99%
“…There seems therefore to be a clear necessity for support and guidance from several different stakeholders with varied responsibilities to collaborate in supporting these needs (e.g. [18,36]). An additional challenge described was that of identifying ongoing funding for services [25,38].…”
Section: Needs and Challenges In An Educational Contextmentioning
confidence: 99%
See 3 more Smart Citations